PENGEMBANGAN WISATA SITU CINANGSI BERBASIS WEBSITE : PENGEMBANGAN WISATA SITU CINANGSI BERBASIS WEBSITE - Aji Kurnia; Sendy Perdana Firdiansyah; Muhamad BayuAji; Abdul Aziz; Dede Sahlan; Hilmi Surowardi; Moh Budi Nurcahyono; Muhamad Sulaiman; Panji Mohammad; Bayu Surya (CV. Multi Kreasi Media, 2022)
Making Information Media for Website-Based Situ Chinangsi Tourism Development. The world of the Internet is increasingly developing, because humans are always looking for new breakthroughs in the development of a remote information system that provides access rights and detailed information for the community. Business competition in various business sectors is supported by the rapid development of information technology. Likewise, the information media for web-based tourism development, especially information about natural tourism in the village, is one located in Cikuda Village, Parungpanjang District, Bogor Regency, West Java Province. So far, new tourism promotion media and price changes are still being conveyed by telephone and brochures, so the information conveyed is not fast and complete. Meanwhile, booking tours are still done in the conventional way. Therefore, a web-based tourism development information media system is needed to provide convenience to the community. Apart from being a medium to promote tourism, this information provides convenience to the public for the desired tourist information media. With this media, it is hoped that customers can see the latest information on Situ Chinangsi Tourism if there is a change along with the price.